The association between betel quid use and oral potentially malignant and malignant disorders in Southeast Asian and Pacific regions: a systematic review and meta-analysis with GRADE evidence profile - Jasim, Aula; Li, Xia; Octavia, Alfini; Gunardi, Indrayadi; Crocombe, Leonard; Sari, Elizabeth Fitriana (Frontiers in Oral Health, 2024)
Background Betel quid (BQ) chewing is a prevalent habit in the Asian and Pacific regions. It is deeply intertwined within cultural customs, and has been reported to result in oral potentially malignant disorders (OPMDs) and malignant disorders (MDs). Objective We aim to present a summative and broad overview of the burden that BQ chewing has imposed on the residents of the Southeast Asian, Pacific, and Australasian regions, allowing us to quantify the level of impact it is currently causing on the risk of people developing oral cancer. Methods This scoping review and meta-analysis screened databases such as PubMed, MEDLINE, and Google Scholar for publications that investigated the association between BQ and OPMDs and MDs. The search strategy involved MeSH headings relating to BQ, OPMDs, and MDs, and a search for results during the period between January 2010 and June 2023 within the set geographical boundaries of the Southeast Asian and Pacific regions. This systematic review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement for Scoping Reviews (PRISMA-ScR). R software was used to screen outliers. The included studies were further analysed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. Results Nine articles (n = 19,312 participants) presented odds ratio outcomes from 11 regionally different study groups. We indicated a strong correlation between BQ chewing and the increased risk of OMPDs and MDs. The risk was quantified through meta-analyses with an odds ratio (OR) of 8.18 (5.27–12.72) and an increased OR of 9.93 (7.36–13.39) when the outlier was removed. BQ chewing was further identified within various Australian communities and discovered to be produced locally in North Queensland. Discussion A meta-analysis of two outcomes revealed substantial heterogeneity and minor evidence of publication bias, thus the association effect was included with and without these articles. The overall GRADE quality of evidence ranged from moderate to very high and highlighted five studies with a high level of imprecision. Conclusion The lingering high prevalence of BQ in the Southeast Asia and Pacific regions, as well as its rising acceptance among non-ethnic Australians, is alarming and requires prompt and rigorous intervention to prevent the risk of oral cancer. Systematic Review Registration PROSPERO (CRD42023429694).